ANALISIS FAKTOR KESEHATAN DAN KESELAMATAN KERJA (K3) YANG SIGNIFIKAN MEMPENGARUHI KECELAKAAN KERJA PADA PROYEK PEMBANGUNAN APARTEMENT STUDENT CASTLE - Saloni Waruwu; Ferida Yuamita (Universitas Ahmad Dahlan Indonesia, 2016)
Health and Safety (K3) is an effort to create a safe working atmosphere, comfortable and achieve thegoal of maximum productivity. K3 is very important to be implemented in all areas of employment withoutexception building projects such as apartments, hotels, malls. However, to prevent any risk of workplaceaccidents is not as easy as turning the palm of the hand. Occupational accidents disebab by severalfactors, among others, occupational safety and health training (X1), the commitment of top management(X2), work environment (X3), awareness of workers (X4), regulations and safety and health procedures(X5), availability rambu- occupational health and safety signs (X6) in the workplace, and communicationworkers (X7). The most significant factor affecting the accidents are the top management commitment(X2) with a value of 36.4% koefien regression and awareness of workers (X4) of 30.1%. If both of thesefactors add up the total is 66.5%. Keywords : occupational accident, health and safety factor, significantly.